(untitled) (Palimpsesto, 2021)
This work is intended to explore tales reliving events of March 24th, 1976, on the basis of Ricardo Piglia’s concept of detachment for the 21th-Century narratives and Benjaminian ideas of now-time, constellation saturated with tension and brushing history against the grain. In view of that purpose, this piece is built upon three texts from Golpes. Relatos y memorias de la dictadura, a book published by Miguel Dalmaroni and Victoria Torres 40 years after Argentina’s last coup. Those texts evoke “the collective trauma that will never cease to appeal to us” from the perspective of Argentine writers born between 1957 and 1973.